Outcomes of international student mobility programs: a systematic review and agenda for future research. Issue 9 (2nd September 2019) - Roy, Achinto; Newman, Alexander; Ellenberger, Tori; Pyman, Amanda
ABSTRACT: Scholarly studies of international student mobility programs have increased during the last two decades, particularly following the Bologna Declaration. Nevertheless, a systematic review of international student mobility programs and the outcomes and benefits derived from participation in such programs has not been undertaken. This paper provides a comprehensive review of studies examining the various outcomes of student participation in short-term international mobility programs and identifies under-researched areas such as employment and career outcomes. A future research agenda based on the review is outlined, along with recommendations for improving research designs in order to increase our understanding of the short- and long-term outcomes of international student mobility programs.